2017
DOI: 10.1177/0306624x17741803
|View full text |Cite
|
Sign up to set email alerts
|

“The Whole Is Greater Than the Sum of the Parts”: Prison Staff Perceptions of Domestic Violence Rehabilitation Programs

Abstract: This qualitative study is part of a mixed methods research project that examined the effectiveness of the primary rehabilitation program for domestic violence offenders in the Israeli Prison Services-the "House of Hope." The quantitative part of the study showed that the "House of Hope" program was effective in reducing recidivism among participating inmates. The purpose of this qualitative study was to describe the rehabilitation program according to the perspectives of the program staff. For this purpose, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The researchers found a significant correlation between incorporating the three principles in formulating a treatment program and reducing recurrent imprisonments (Andrew & Bonta, 2010). Thus, for example, a research study that examined the treatment package administered to prisoners found a significantly lower incidence of recurrent imprisonments during 4 years following participation in the rehabilitation program (Shoham et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found a significant correlation between incorporating the three principles in formulating a treatment program and reducing recurrent imprisonments (Andrew & Bonta, 2010). Thus, for example, a research study that examined the treatment package administered to prisoners found a significantly lower incidence of recurrent imprisonments during 4 years following participation in the rehabilitation program (Shoham et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, paroled prisoners cannot be hired by relatives or employers with a criminal background. In addition, other than in rare cases, paroled prisoners must work as salaried employees even if they were self-employed before their imprisonment (Shoham et al, 2017). In light of these restrictions, it seems safe to assume that the employment difficulties reported by the study participants stem, at least partially, from the restrictive parole conditions, which unfortunately add to the employment difficulties generally encountered by released prisoners (Peled-Laskov et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As part of an attempt to address this recidivism issue, together with the growing emphasis on prisoner rights, prisons in the Western world offer a variety of rehabilitation programs aimed at assisting people who are incarcerated and ex-prisoners with recovery and reintegration into society through the acquisition of certain life skills (Andrews et al, 1990(Andrews et al, , 2011Enosh et al, 2013;Lipsey & Cullen, 2007;MacKenzie, 2006;McGuire, 2003;Shoham et al, 2017Shoham et al, , 2018. The objectives of such programs include, inter alia, changing prisoners' state of mind, reducing risk factors in their lives, and developing prosocial skills, which, in turn, are designed to reduce and stop antisocial behaviors (Ross, 1980;Ross & Hilborn, 2008).…”
Section: Introductionmentioning
confidence: 99%